THE POSITION AND THE ROLE OF THE TEACHER IN PERSPEVTIF OF ISLAM EDUCATION - Mayada Rahma, Soci; Nur Hanifah, Muthi’; Salsabila, Cut Putri; Batubara, Zaidan Zuhdi; Farhan, M. Rafiqi (Proceeding International Seminar of Islamic Studies, 2023)
The teacher is the most important role in learning process, because a teacher will change behavior and improve the quality of students to become better individual. The duty of a teacher is to guide, educate, and direct students to always be devoted to Allah SWT. In Islam the figure of religion teacher is very strategic, in addition to carrying out a scientific mission so that students master religious sciences, the teacher also carries out a sacred duty, a prophetic mission, namely to guide and direct students towards the path of Allah SWT. This article aims to find out that teachers have a higher and special position in the perspective of Islamic education. The research approach used in this article is qualitative research. This study uses library data sources in obtaining data. This study uses library data sources in the form of books, journals, and other sources collected from several references related to the title of this article. The technique used in data collection is by finding reference sources related to the discussion of this article, then analyzing the contents of the data that has been collected. The results of this study indicate that teachers have a higher position in an Islamic perspective. Allah will also give higher positions and degrees to knowledgeable people. A teacher has an obligation in order to create the nation's children to become intelligent human beings and have good morals.